Analisis Faktor-Faktor Yang Mempengaruhi Hasil Belajar Siswa Pada Masa Pandemi Covid-19 Di SMK Kota Padang (Studi Pada Siswa di SMKN 3 Padang dan SMKS Nusatama Padang) - Widya Annisa Putri; Rino Rino (Universitas Negeri Padang, 2023)
This study objective to identify the factors that influence student learning outcomes during the Covid-19 pandemic at Smkn 3 Padang and Smks Nusatama Padang. The population in the research is 1801 students of Smkn 3 Padang and Smks Nusatama Padang and the sample is 95 students obtained using Proportional random sampling technique. The data is collected with questionnaire from 95 respondents who doing online learning during covid-19. The data will be analyzed using factor analysis. The result of the analysis show that school factors and parenting, and self-potential factors are the factors that influences student learning outcomes during the covid-19 pandemic at Smkn 3 Padang. And the result of the analysis show that instrumental factors, learning facilities factors, discipline and parenting factors, personal factors are the factors that influences student learning outcomes during the covid-19 pandemic at Smks Nusatama Padang.